Level Perception of Elementary School Students Towards Food in The School Environment of Banyuwangi Public Elementary School 2 Tukang Kayu - Utami, Arfiati Ulfa; Setyawan, Bagus; Chastelyna, Agnes Juniarti; Arista, Yuvita Lira Vesti; Ulfa, Rosiana (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Elementary school students' understanding of healthy food is very important because this will have an impact on the health of students and the school environment. This study aims to measure the extent to which students' perceptions of snacks in the school environment at SD Negeri 2 Tukang Kayu Banyuwangi. This research used survey method. The subjects in this study were 50 fifth grade students of SD Negeri 2 Tukang Kayu Banyuwangi. The research instrument was a questionnaire or questionnaire sheet. The analysis used is descriptive qualitative. The results of student perceptions obtained 72% of students can understand healthy snacks in the school environment.